IMPACT OF FUNCTIONAL-TRUE OPERATIONS FOR THE CONTENT OF NATURAL LANGUAGE SENTENCES - Вавіленкова, А. І. (Science-based technologies, 2016)
The article considers complex natural language sentence as atomic predicates, and functional-true operations between them effect on representation of content of sentences. The article analyzes the validity of logical statements and defines the formal conditions under which two atomic predicates can be considered identical. Transactions in which complex conditions are formed from simple ones considered to be functional-true and directly impact on representation of logiс and linguistic model of content of natural language sentences. The study analyzes certain forms of logic and linguistic models of text information as well as formation of semantic relationships between concepts of natural language sentences. For each functional-true operation there are defined conditions when logic operation incorrectly interprets the semantic links that has been demonstrated by examples. For each functional-true operation there is a certain form of separate logic and linguistic model. The formulation of the basic principles of usage of logical operations according to semantic relationships between concepts allows to form identity rules of natural language sentences to their further comparison by content.